2009
DOI: 10.2166/wst.2009.442
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of water, sanitation and health: a case study from the Mekong Delta, Vietnam

Abstract: In the Mekong Delta in the south of Vietnam about 5.7 million people lack access to safe drinking water and 10 million people in rural areas live without adequate sanitation. Between May and August, 2007 a survey was carried out in An Bin, a peri-urban ward in the Mekong Delta, to gain insight into water, sanitation and health as well as to health-related hygiene behaviour. The study employed a combination of quantitative (standardized questionnaire) and qualitative (focus group discussions, semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…22 Una expresión específica de los procesos de la globalización se encuentra en al menos tres aspectos interrelacionados que emergen en los GF: por una parte, la publicidad utiliza elementos comunes en la propaganda mundial que son reportados en diversos estudios como aspectos de salud, estilo de vida y características del agua, mediante el uso de adjetivos similares como saludable, limpia, pura y benéfica para la salud. 14,16,18,20,23 Un segundo aspecto es el agua embotellada y las BA como parte de prácticas de consumo y de la toma de decisiones no siempre orientadas a prácticas saludables; y un tercer aspecto es la relación de los dos anteriores con elementos más locales como las prácticas culturales, condiciones de trabajo y servicios públicos.…”
Section: Discussionunclassified
“…22 Una expresión específica de los procesos de la globalización se encuentra en al menos tres aspectos interrelacionados que emergen en los GF: por una parte, la publicidad utiliza elementos comunes en la propaganda mundial que son reportados en diversos estudios como aspectos de salud, estilo de vida y características del agua, mediante el uso de adjetivos similares como saludable, limpia, pura y benéfica para la salud. 14,16,18,20,23 Un segundo aspecto es el agua embotellada y las BA como parte de prácticas de consumo y de la toma de decisiones no siempre orientadas a prácticas saludables; y un tercer aspecto es la relación de los dos anteriores con elementos más locales como las prácticas culturales, condiciones de trabajo y servicios públicos.…”
Section: Discussionunclassified
“…Tackling diarrhea has been less successful over the last twenty years (Lincoln 2014;Trach et al 1997;Van Man et al 2005). Diarrheal disease is difficult to document, as most cases get treated at home or by private practitioners, and thus do not enter official health records (Kotsila Journal (Cairncross et al 2013;Rheinländer et al 2010) Previous studies on the Mekong Delta have indicated that the links between water, sanitation and hygiene are poorly understood, increasing people's exposure to diarrheal disease (Herbst et al 2009;Reis and Mollinga 2012). Public health information and education around the issue is poor or insufficient, and the diarrhea challenge is still significant.…”
Section: Journal Of Political Ecologymentioning
confidence: 99%
“…Also the Mekong basin is experiencing strong population growth, development and more intensive farming practices (Baran and Jantunen 2005;Liljeström et al 2012; Navy and Bhattarai 2009). More intensive upstream agricultural activities threaten to increase the nitrate levels (Baran and Jantunen 2005;Herbst et al 2009;Navy and Bhattarai 2009;Udomchoke et al 2010;Yen et al 2007) in the source waters. Currently, the water treatment plants have no capacity to reduce nitrate levels so any increase in nitrate in the supply water will be passed onto consumers.…”
Section: Future Threats To Water Qualitymentioning
confidence: 99%